(untitled) (The Peerian Journal, 2025)
This article examines certain types of external population migration as risk factors for the emergence of outbreaks of especially dangerous infectious diseases in the Republic of Uzbekistan and the Central Asian region. The role of tourism and labor-related cross-border migration in shaping the epidemic manifestations of infectious diseases is highlighted. The importation of influenza caused by new virus subtypes, cholera, poliomyelitis, hemorrhagic fevers, anthrax, brucellosis, and others is becoming increasingly relevant for these regions.